Chyle Leak after a Simple Hemithyroidectomy: An Extremely Rare Situation - Muhammed, Adi S; Suhaimi, Shahrun N; Othman, Suraya; Rashid, Nor Faezan A; Muhammad, Rohaizak (IIUM Medical Journal Malaysia, 2019)
Chyle leak is a well-known complication that can occur after a thyroidectomy with neck dissection; however, it rarely occurs after thyroidectomy alone. Here, we report a case of chyle leak following a left hemithyroidectomy for a benign solitary thyroid nodule. Based on the literature search, this is only the second reported case of a chyle leak after a simple hemithyroidectomy without any central or lateral neck dissection. Amongst the possible causes, we hypothesize that the use of intraoperative nerve monitor may be a contributing factor. Treatment options are explored and the patient was treated successfully with nonoperative management.